Narrativa em fragmentos: as ruínas do Patu e as memórias sobreviventes - Cleiviane Marques Vasconcelos (2024)
This study is limited to the Patu concentration camp, in Ceará, where there are ruins that served as the setting for the 1932 drought tragedy. More than ninety years after this event, what remains are fragments that are expressed in old buildings, in testimonies, in memories and also in forgetfulness. Thinking about ruins as experiences linked to the past, we are interested in their poetic dimension as gaps that perhaps allow us to access not only the memory, but also its temporalities. To this end, the main objective of this research was to understand how the temporalities of the memories about the Patu concentration camp are constructed, based on the poetic proposition of an artistic work based on narratives that intertwine ruins, testimonies, memory and oblivion. This is a creative research, carried out based on previous studies, documents, files and interviews that seek to describe, but also interpret the Patu concentration camp based on the experiences of the subjects.